Music, dance, and negotiations of identity in the religious festivals of Bicol, Philippines - Adiova, Marilyne Antonette
This dissertation examines the relationships between music, dance, faith, memory, the objectification of tradition, and tourism found in religious festivals in Bicol, Philippines. The three case studies of this dissertation explore festivals as complex, ever-changing phenomena that are shaped in many ways by the dynamic between religious and secular communities. The first case study discusses the shift of the Tinagba Festival in Iriga City, Philippines from a community festival into a regional event, and examines the tensions that exist between the Catholic Church, local government, and private sector in its planning. The second case study examines the push and pull between the Church and the local government over the Feast of Our Lady of Penafrancia in Naga City. The third case study discusses the roles of memory and music in the staging of the Feast of Our Lady of Penafrancia in Michigan and the ways in which members of a Bicolano diaspora community reconstruct and modify aspects of culture through shared memories, music performance, and current circumstances. The analyses in this study give particular attention to street dancing competitions, as these events are highlights of almost every Philippine festival on local, regional, and national levels. Street dancing competitions consist of music and dance choreography that portray aspects of culture meant to represent traditional and regionally specific aspects of Bicol. Participants are judged on the music performed and the coordinated movements of the dances. While judges look for creativity among the competing groups, they also adjudicate how well groups espouse the values and identity of the community and region they represent. This study argues that festivals are not merely occasions of celebration that provide breaks from the everyday and the mundane; they also bring to the fore the continuous negotiation of tensions between the most powerful institutions of the region: religion and government, and the man.